TLR3 rs3775291 C/T polymorphism is associated with elevated IFN-α level in asymptomatic HTLV-1 infection - Ferreira, Fabiane dos Santos; Brito, Wandrey Roberto dos Santos; Santana, Emmanuelle Giuliana Mendes; Oliveira, Aline Kelly Alves; Lima, Aline Cecy Rocha de; Amoras, Ednelza da Silva Graça; da Costa, Carlos Araujo; Souza, Maísa Silva; Lima, Sandra Souza; Ishak, Ricardo; Cayres-Vallinoto, Izaura Maria Vieira; Vallinoto, Antonio Carlos Rosário; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAlterations in the immune response may influence the development of HTLV-1-associated diseases. TLR3 detects viral nucleic acids, including HTLV-1, and triggers the production of IFN-I and other cytokines. Genetic variations in TLR3 may alter the antiviral and inflammatory responses and contribute to the progression of HTLV-1 infection. The present study investigated the association of polymorphisms in the TLR3 gene (rs5743305 T/A and rs3775291 C/T) with HTLV-1 infection status and their relationship with infection-associated diseases, receptor expression levels, proviral load, and inflammatory and antiviral cytokines.MethodsBlood samples were collected from 179 individuals with HTLV-1 infection (82 with inflammatory diseases and 97 asymptomatic individuals) and 179 controls. Genotyping of polymorphisms, analysis of TLR3 gene expression, and quantification of proviral load were performed by real-time PCR, and cytokine levels were measured by enzyme-linked immunosorbent assay (ELISA).ResultsThe polymorphisms showed no correlation with susceptibility to HTLV-1 infection, or the occurrence of disease symptoms linked to the infection. The presence of disease symptoms was associated with higher TNF-α levels and proviral load. TLR3 rs5743305 T/A polymorphism was not associated with variations in TLR3 and IFN-α levels. For the TLR3 rs3775291 C/T polymorphism, asymptomatic individuals carrying the TT polymorphic genotype presented significantly higher IFN-α levels and lower proviral load. The profile of asymptomatic individuals carrying the polymorphic genotypes for TLR3 rs3775291 C/T was characterized by higher levels of TLR3 and IFN-α and lower levels of proviral load, TNF-α and IL-6 compared to those with the wild-type genotype.ConclusionAlthough polymorphisms in the TLR3 gene have not been associated with the presence of symptoms of HTLV-1-related inflammatory diseases, the TLR3 rs3775291 C/T polymorphism appears to contribute to a better evolution of the HTLV-1 infection status and inflammatory process among asymptomatic individuals.